Demokracja wewnątrzpartyjna po 25 latach przemian na przykładzie wyborów powszechnych Przewodniczącego Platformy Obywatelskiej RP w 2013 roku - Pawłowski, Marek (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
This article attempts to characterize the general election for the Chairman of the Polish political party Platforma Obywatelska RP in 2013. In article described new law and compared technological solutions in the online vote. The results of the analysis indicate that these elections are by far the most advanced model of e-voting in Poland, which could become the basis, after pulling critical applications, the introduction of such solutions in the presidential elections, parliamentary or local government. At the same time it seems that the direct election of the head of the party, not only at the national level, a positive impact on its operation, allowing you to avoid many risks, especially political corruption.